(untitled) (Journal of the College of Basic Education, 2022)
Polycrystalline layers of Lead iodide have been prepared using a spray technique on glass substrates for potential application to nuclear detection .This paper studied The influence of changing substrate temperature of PbI2 films on the structural, optical and electrical properties has been investigated at Different substrate temperature (150.200.250)ₒC.